The financial situation of cities with poviat rights in Eastern Poland vs. diversification of development potential - Dziekański, Paweł (Sytuacja finansowa miast na prawach powiatu Polski Wschodniej a zróżnicowanie potencjału rozwojowego, 2019)
Cities with ‘powiatʼ (county) rights are a specific combination of commune and powiat self-governments. They carry out both the tasks of the commune and powiat. To this end, they create their own financial policy. Local finances, as a resource of the individual, become a development factor. Finances are the basis for the implementation of public tasks and determine the conditions for economic development. The rate and structure of income that determine investment activity have a decisive impact on the pace of socio-economic development. The conditions of the financial situation may be shaped by the area (e.g. location and size of local government units, available resources and natural values, investment attractiveness) and may also be independent of it (e.g. economic fluctuations in (the country and in the world, the state of public finances, the scope of income control) and expenditure LGUs)
Biblioteka Regionalisty, 2019, Nr 19, s. 50-65
Keywords: Dolny Śląsk